Răspuns :
Explicație pas cu pas:
4.
a)
[tex]x = ( \frac{2}{ \sqrt{12} } + \frac{9}{ \sqrt{27} } + \frac{6}{108} ) \times ({ \frac{1}{ \sqrt{ 3} } })^{ - 1} \\ x = ( \frac{2}{2 \sqrt{3} } + \frac{9}{3 \sqrt{3} } + \frac{6}{6 \sqrt{3} } ) \times \sqrt{3} \\ x = ( \frac{1}{ \sqrt{3} } + \frac{ 3}{ \sqrt{3} } + \frac{1}{ \sqrt{3} } ) \times \sqrt{3} \\ x = \frac{1}{ \sqrt{3} } \times \sqrt{3} + \frac{3}{ \sqrt{3} } \times \sqrt{3} + \frac{1}{ \sqrt{3} } \times \sqrt{3} \\ x = 1 + 3 + 1 = 5 [/tex]
b)
[tex]y = ({5}^{6} ) {}^{3} \times {25}^{3} \div {125}^{8} \\ y = {5}^{18} \times {5}^{6} \div {5}^{24} \\ y = {5}^{0} = 1[/tex]
[tex]ma = \frac{x + y}{2} = \frac{5 + 1}{2} = \frac{6}{2} = 3 - nr \: prim[/tex]